Glocal Bodies: Dancers in Exile and Politics of Place: A Critical Study of Contemporary Iranian Dance - Hatami, Elaheh (transcript, 2022)
This book is a critical study of Iranian dance and the works of Iranian-American female dancers in exile. Focusing on the study of contemporary Iranian dance through analysis of the choreographies of three female dancers in diaspora (namely Aisan Hoss, Shahrzad Khorsandi, and Banafsheh Sayyad), this research is among the first of its kind. Elaheh Hatami investigates the transformation of professional Iranian dance and discusses the role of relocation and displacement in its performance. She argues that Iranian dance and Iranian female dancers have always been in exile – not only in a physical sense, but also in the metaphorical sense of ›exile‹ implying foreignness, exclusion, and marginalization.